2021
DOI: 10.1097/wnf.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Minocycline for the Treatment of Methamphetamine-Induced Psychosis and Cognitive Impairments: An Open-Label Case Series

Abstract: Aim Methamphetamine-induced psychosis and neuropsychological impairments are common among patients with methamphetamine use disorder. Given some preclinical and clinical studies reporting potential effects of minocycline, a second-generation tetracycline, on correcting manifestations of drug addiction, this study aimed to examine the effectiveness of minocycline in attenuating psychotic symptoms and neuropsychological impairments in chronic methamphetamine users. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Several studies have shown that inhibitors of microglial activation such as minocycline can suppress pro-inflammatory cytokine expression and restore hippocampal neurogenesis, as well as ameliorate depressive-like behaviors and cognitive impairment ( Zhang et al, 2020b ; Alavi et al, 2021 ; Bassett et al, 2021 ). Our results are consistent with the observation that variations in the relatively small number of new neurons in adult brains of humans and rodents is strongly linked to the pathogenesis and remission of neuropsychiatric disorders ( Grace et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that inhibitors of microglial activation such as minocycline can suppress pro-inflammatory cytokine expression and restore hippocampal neurogenesis, as well as ameliorate depressive-like behaviors and cognitive impairment ( Zhang et al, 2020b ; Alavi et al, 2021 ; Bassett et al, 2021 ). Our results are consistent with the observation that variations in the relatively small number of new neurons in adult brains of humans and rodents is strongly linked to the pathogenesis and remission of neuropsychiatric disorders ( Grace et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%